Cybernetics and the philosophy of mind - Sayre, Kenneth M. (Routledge and Kegan Paul, 1976)
This book, published in 1976, presents an entirely original approach to the subject of the mind-body problem, examining it in terms of the conceptual links between the physical sciences and the sciences of human behaviour. It is based on the cybernetic concepts of information and feedback and on the related concepts of thermodynamic and communication-theoretic entropy.